Proses Perencanaan Anggaran Desa di Desa Sayang Kecamatan Jatinangor Kabupaten Sumedang - Mas Rasmini; Riri Fariroh Firdau (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
Village development plays an important role in improving the well-being of the people. According to the Law No. 6 of 2014 the village is the basis of development and is given the authority to regulate and manage its interests independently. It is important for the village to manage its finances effectively and optimally so that the village can plan and implement the village development programmes sustainably. However, the problem that has occurred in Sayang Village, Jatinangor District, Sumedang District is the late receipt of pagu and budget information from the district/city that can hinder the budget planning process. The study aims to analyze the budget planning process in Sayang Village, Jatinangor district, Sumedang district using qualitative methods. Data was obtained through observations, interviews, and supporting documents. The results of the research showed that despite the delay in receiving pagu and budget information, Sayang Village was able to perform budget planning according to the theory (Mahsun, 2019) well at every stage. This research provides academic and practical advice to improve the budget planning process at the village level.